Disability on a Different Model Glimpses of an Asian Heritage - Miles, M. (2002)
The paper reviews common uses of disability models and terminology, then sketches a few social responses in historical Zoroastrian, Jaina and Daoist philosophies. In a discussion of the ‘merits of uselessness’, Chuang-tzu's holistic social model is reconstructed. A Buddhist tale of ‘hunchback Khujjutara’ suggests that karma may be seen as an educational rather than retributive force. Contested histories of blind Japanese and Chinese people, and the dramatic enactment of contradictory behaviours towards them, support the view that Asian meanings of disablement should not be forced into modern European categories but may challenge and refresh them.
Keywords: Asia; Buddhist; China; Daoist; Disability; India; Jaina; Japan; Zoroastrian; Models; social responses; Terminology